Second-generation biofuel production from the organic fraction of municipal solid waste - Kowalski, Zygmunt; Kulczycka, Joanna; Verhé, Roland; Desender, Luc; De Clercq, Guy; Makara, Agnieszka; Generowicz, Natalia; Harazin, Paulina (Frontiers in Energy Research, 2022)
Biofuels are playing an increasingly important role since they are an attractive alternative to fossil fuels, access to which has been limited. Moreover, they can help the European Union countries meet their climate and energy objectives. There is a growing interest in the production of biofuels from the organic fraction of municipal solid wastes as second-generation biofuels. Such a solution supports a circular economy as an example of an effective approach in terms of effective waste management. The study presents a review of different biofuels with an emphasis on second-generation biofuels from lignocellulose biomass, highlighting the BioRen process, which is one of the waste-to-fuel conversion technology. It allows for maintaining the value of materials within the economy. All stages of the process are described and material flow is presented. The framework of the BioRen project includes the bio-fermentation of the organic fraction by a two-stage enzymatic process simultaneously into bioethanol and isobutanol, which are then used to produce glycerol tertiary butyl ether. The post-fermentation sludge is treated by the hydrothermal carbonization method increasing the efficiency of the whole waste treatment process and closing the loop. The bio-coal resulting from the process of carbonization can be used as a fuel with a high calorific value. The remaining fraction undergoes a physical-chemical and catalytic conversion of inorganic particles into their clean, dry, and inert components. The results show that in the BioRen project 78% of the heat that is produced during the process is recovered and used for electricity production. Moreover, 53% of waste is recovered and re-used, due to the process is profitable, efficient, environmentally friendly, and maintains high-security standards. Such an example of advanced technology, with a high readiness level, obtained results, and experience may encourage European countries and facilities to implement such an effective solution, which supports the development of bioenergy.